Phytonematodes Community and Polyphasic Character of Aphelenchoides varicaudatus on Garlic Plants in Tegal Regency, Central Java - Mokhammad Danang Kusuma; Supramana Supramana; Giyanto Giyanto (Universitas Gadjah Mada, 2020)
The interception of Ditylenchus dipsaci, D. destructor, and Aphelenchoides fragariae, which are classified as quarantine pests, has been reported to occur on imported garlic bulbs used for consumption at several traditional markets in Bogor. This finding should increase awareness of the chance of garlic contamination in Indonesia’s garlic fields. This study aimed to evaluate the nematode community and determine polyphasic characters of Aphelenchoides species from garlic plantations. The study was conducted by sampling soil and plants from garlic plantations in Tuwel and Rembul Villages, Bojong District, Tegal Regency, Central Java in December 2018. Nematode extraction was done using a mist chamber for plant materials and sugar flotation – centrifugation methods for soil samples. Parameters measured included nematode species identity, absolute population and prominence indexes. Nematode identification was conducted based on their morphological characters. Further identification based on morphometric and molecular characters (polyphasic) conducted for nematodes species suspected as quarantine pests. Six generas of nematodes identified were Helicotylenchus, Aphelenchoides, Rotylenchulus, Aphelenchus, Criconemoides, and Tylenchus. Aphelenchoides sp. had the highest prominence value from plant tissue with a value of 6.32 and is categorized as a quarantine pest genus (A. fragariae) in garlic and was further identified to the species level. Further identification based on polyphasic characters showed the Aphelenchoides sp. found was A. varicaudatus.